Escola de Gestores, o curso de especialização em gestão escola no estado de Alagoas: Fala Gestor! - Brito, Maria Betânia Gomes da Silva (2017)
This thesis is based on the study on the Specialization Course in School Management of the National School Program of Public Basic Education Managers (PNEGEBP), in the state of Alagoas. The general objective was to reveal to what extent this course has contributed or not to the strengthening of democratic management in the Alagoas public school during the period from 2007 to 2016, when the course offered three editions by the Federal University of Alagoas (UFAL ), starting from the premise that the formation causes superficial changes in the school management and contributes to a timid improvement in the management processes of the public school. To do so, a qualitative approach was adopted, based on interviews and questionnaires with the coordinating teachers of the course and with the managers of the public schools who were students. In the absence of specialized managers of the specialization, were consulted school coordinators who are part of the management team of the teaching unit in focus. The analyzes of interviews, questionnaires, documents, census and service data were made possible by content analysis and statistical surveys. In order to justify the research, a brief presentation was presented of surveys conducted by the country from the beginning of PNEGEBP, based on data from the Bank of Thesis / Summaries of the Coordination for the Improvement of Higher Education Personnel (Capes) and publications of the National Association of Education Policy and Administration (ANPAE). The theoretical framework is based mainly on the following authors: Oliveira (2009); Oliveira and Rosar (2010); Krawczyk and Wanderley (2003); Krawczyk and Vieira (2008); Krawczyk, Campos and Haddad (2000); Paro (2012); Ferreira (2011); Ferreira and Aguiar (2011); Libano (2004); Cervi (2013); Tardif and Lessard (2005); Calderano and Lopes (2006); Bruno, Calderano and Teixeira (2010); Geraldi, Fiorentine and Pereira (1998); Serbino et al. (1998); Scholze, Almeida and Almeida (2007); Colares, Estrela and Pacífico (2009); Schwartz, Araújo and Rodrigues (2010) and Teixeira (2011). The concepts of "democratic management", "training of school administrators", "participation and autonomy" constituted categories of analysis, drawn from the corpus itself. Throughout the analysis, it was possible to identify significant contradictions in relation to the Specialization Course in School Management, among which the following stand out: convergences and divergences, referring to the educational reforms and the policies directed to the public school management in Alagoas, as well as lack of quantitative / qualitative data on the demand and performance of the trainees. Even so, the course presented positive aspects, among which the organization of an integrated training process between the universities and local education bodies, capable of attending to the real demands of the students; as negative aspects, regarding future prospects, insecurity about the continuity of the Program, as it is a government initiative, is not associated with the management policy of public schools, mainly in the state of Alagoas, where a management format predominates by indication, which is configured, in the current neoliberal context, as a challenge for the formation of school managers. In addition, this thesis presents possible actions that may aid in this construction and indications for future research.